Heat Transfer Rate Optimisation of Ionanofluid Based Heat Sink Using ANSYS - Bakthavatchalam, B. (Universiti Malaysia Pahang, 2020)
Heat dissipation of various electrical and electronic devices has been a significant concern in the current years of modernisation. Many researchers proved that a liquid-cooled microchannel heat sink (MCHS) is an effective way of removing high heat load. Due to ionic liquidsâ unique properties such as negligible volatility, non-flammability, high thermal stability, and ionic conductivity, this liquid is combined with nanofluids to synthesise a new class of potential fluids termed Ionanofluids (ionic liquid-based nanofluids). In this research, a numerical simulation of fluid flow and heat transfer characteristics of MWCNT (Multiwalled Carbon Nanotubes) based Ionanofluids as a coolant in a rectangular-shaped microchannel heat sink is analysed. The Two-step method is used for preparing the studied Ionanofluids consisting of 0.5 wt. of MWCNT nanoparticles ultra-sonicated with a mixture of propylene glycol and 1-Butyl-3-methylimidazolium chloride (BmimCl-ionic liquid) fluids. Copper micro channelled heat sink comprising 1 m channel height, 25 Âµm of channel diameter, and 0.7 m channel width is modelled and simulated with ANSYS-Fluent. The results showed that the heat transfer coefficient increases about 11.4% while the thermal resistance decreases about 15.18% by using the proposed ionanofluids with the concentration of 0.5 wt.% at Re=2000 compared with that of an MCHS with propylene glycol. Moreover, the pressure drop along the studied MCHS increased up to a maximum of 30 kPa for higher heat gradients. Ionanofluids decreased the thermal resistance and temperature difference between the heated surface of the MCHS and Ionanofluids inlet to a greater extent when validated with pure base fluid and previous studies. From the simulated results, a better cooling performance is observed with Ionanofluids compared to pure propylene glycol (PG) for the proposed microchannel heat sink. Â© The Authors 2020. Published by Penerbit UMP. This is an open access article under the CC BY license.